Interplay of Biochemical, Genetic, and Immunohistochemical Factors in the Etio-Pathogenesis of Gastric Ulcer in Rats: A Comparative Study of the Effect of Pomegranate Loaded Nanoparticles Versus Pomegranate Peel Extract - Abd el-Rady, Nessren M.; Dahpy, Marwa A.; Ahmed, Amel; Elgamal, Dalia A.; Hadiya, Safy; Ahmed, Mai A. M.; Sayed, Zain El-Abdeen Ahmed; Abdeltawab, Doaa; Abdelmohsen, Ahmed Shawkat; Farrag, Alshaimaa Abdelkhaliq Mohammad; Ashmawy, Ahmed M.; Khairallah, Marwa K.; et al. (Frontiers in Physiology, 2021)
Background Few data are available about the role of herbal extract loaded nanoparticles as an alternative safe medicine for the management of a gastric ulcer. Aim This work is targeted at exploring the physiological effects of pomegranate loaded nanoparticles (PLN) against an indomethacin IND-induced gastric ulcer and comparing the results with traditional pomegranate peel extract (PPE). Methods Twenty-four rats were equally distributed into four groups: control, IND-treated, PLN-treated, and PPE-treated groups. Gross examination of gastric mucosa, and the calculation of ulcer and inhibition indices were done. Serum malondialdehyde (MDA), total antioxidant capacity (TAC), interleukin 2 (IL-2), IL-6, IL-10, gastric homogenate prostaglandin E2 (PGE2), and nitric oxide (NO) were estimated. Mucosal endothelial nitric oxide synthase (eNOS mRNA) expression was identified by qPCR. Histological and immuno-histochemical staining of Tumor necrosis factor-α (TNF-α) and eNOS of stomach mucosa were performed. Results In comparison with the control group, IND-treated rats showed visible multiple ulcers with ulcer index, serum MDA, IL-2 and IL-6 were elevated while IL-10, PGE2, NO, and eNOS mRNA expression were significantly reduced. Damaged surface epithelium with disrupted glandular architecture and heavy leucocyte infiltration of lamina propria was noticed. Immunohistochemical staining of stomach mucosa revealed marked increased TNF-α and reduced eNOS. Oral administration of PLN and PPE succeeded in improving the gross mucosal picture, and all biochemical, histological, and immunohistochemical alterations. Conclusion Both PLN and PPE potently alleviated IND-induced gastric ulceration via increasing TAC, PGE2, NO, eNOS mRNA, and protein expression. However, the healing effect of PLN was obviously greater than PPE-treated rats.